(untitled) (Journal of Geography and Environmental Management, 2018)
West Kazakhstan oblast has a decent resource potential and prospects of development of this kind of tourism. Agritourism will help solve such problems in the rural areas of West Kazakhstanoblast, the increase in employment, increase income and cultural level of the people, markets and infrastructure development of the area. Of great importance in shaping the opportunities for development and territorial organization of the species agritourism belong to the plant-growing and livestock. In this connection, the authors of this article assesses the opportunities for development and territorial organization of kinds of modern agritourism in the area of plant-growing and livestock production in the context of the administrative districts of West Kazakhstan oblast. In addition, the identified levels of opportunity for development and territorial organization of agritourism in the West Kazakhstan and levels of capability based on local resource base. Are also considered the concept of agritourism and its relationship with agriculture, the role of the economy in rural areas in territorial aspect.